Test-retest reliability of the revised diplopia questionnaire - Mansukhani, Sasha A. (J AAPOS, 2019)
PURPOSE: To evaluate misclassification of diplopia “success” when using a standardized diplopia questionnaire (DQ), and to report test-retest reliability of the DQ. METHODS: We retrospectively identified a cohort of 100 patients with stable strabismus (<5(Δ) change in prism and alternate cover test measurements at distance and near), stable visual acuity, no change in treatment, and no clinical evidence of change, with completed DQ at two consecutive office visits (median, 71 days apart; range, 5–350 days). To evaluate the rate of misclassification of “success” and “not success,” we compared the second to the first administration of the DQ using two established definitions of success: (1) “rarely” or “never” for straight ahead distance and (2) “rarely” or “never” for straight-ahead distance and reading. For DQ test-retest variability, 95% limits of agreement (LOA) and intraclass correlation coefficients (ICC) were calculated on DQ scores (0–100 scale). RESULTS: When defining success as rarely or never diplopic for distance, misclassification occurred in 12 (12%) of 100 (95% CI, 6%−20%). When defining success as rarely or never diplopic for distance and reading, misclassification occurred in 14 (14%) of 100 (95% CI, 8%−22%). The 95% LOA for the DQ score were 35.2 points, and ICC was 0.85 (95% CI, 0.79–0.90). CONCLUSIONS: We have quantified misclassification and test-retest variability when using the DQ dichotomously or as a continuous measure, equipping the clinician to better interpret DQ outcome data in practice and research.